Levels of undernutrition and associated factors among adults receiving highly active anti-retroviral therapy in health institutions in Bench Maji Zone, Southwest Ethiopia in 2018 - Regassa, Tilahun Mekonnen; Gudeta, Tesfaye Abera (Frontiers in Nutrition, 2022)
Background Nutritional issues are common in people with Human Immune Virus (HIV). At some point, almost everyone living with HIV faces challenges in maintaining good nutrition. There is insufficient evidence-based information on undernutrition in adults living with HIV on Highly Active Anti-Retroviral Therapy. Objective To assess the magnitude of undernutrition and associated factors among patients receiving Highly Active Anti-Retroviral Therapy in health facilities in the Bench Maji Zone, southwest Ethiopia in 2018. Methods A facility-based cross-sectional study design was employed from 1 May to 30 June 2018 on 1,007 study subjects and the participants were selected by using a consecutive sampling technique. Five health facilities were selected through a simple random sampling technique. Data were entered into Epi Data Statistical software version 3.1 and analyzed using Statistical Package for Social Sciences (SPSS) software version 21.0. Logistic regression analysis was used to identify factors associated with undernutrition in adults receiving ART. Odds ratios with 95 % confidence intervals were used to examine associations between dependent and independent variables. Result Of the total 1,007 study subjects, 961 participated in the study. More than half of the participants were female (61.2%), 57.2% were married and 42.9% were in the 30–39 years age group. In this study, the level of undernutrition among patients on antiretroviral therapy was 16%. Age ≥50 [AOR 2.5, 95% CI (1.1–5.6)], being single [AOR 2.2, 95% CI (1.4–3.7)], developing gastrointestinal symptoms [AOR 2.6, 95% CI (1.5–4.4)] and in WHO-defined clinical stages III and IV of HIV/AIDS [AOR 2.8, 95% CI (1.3–6.0)] were found to have a statistically significant association with undernutrition. Conclusion Significant numbers of people on highly active antiretroviral therapy in the study area were undernourished. This demonstrated that HIV/AIDs and its treatment directly or indirectly impacted the nutritional status of the patients, who need a critical follow-up from health workers. Age, marital status, progressing to WHO-defined clinical stage of disease, and development of gastrointestinal symptoms were identified as factors that contribute to undernutrition among patients on highly active antiretroviral therapy. The health care workers and experts working at the ART clinic should focus on patient counseling regarding the early prevention, detection, and treatment of opportunistic infections. Early health-seeking behaviors before the AIDs stage and critical follow-up are the first actions to identify undernutrition.